Reliability and clinical feasibility of measuring dual-task gait in the inpatient rehabilitation setting following traumatic brain injury. (2nd December 2019) - Rachal, Lauren; Swank, Chad; Trudelle-Jackson, Elaine; Driver, Simon
ABSTRACT: Background : To prepare patients with traumatic brain injury (TBI) for discharge from inpatient rehabilitation, physical therapists may incorporate dual-task gait activities. Reliability of common dual-task measures for people with TBI in inpatient rehabilitation is undetermined. Our purpose was to assess inter-rater and intra-rater reliability and clinical feasibility of dual-task measures [Walking While Talking Test (WWTT), Modified Walking and Remembering Task (mWART), Timed Up and Go-cognitive (TUG-COG)] in inpatient rehabilitation for patients with TBI. Methods : A total of 22 individuals with TBI completing the dual-task measures (WWTT, Walking and Remembering Task (WART), and TUG-COG) in inpatient rehabilitation were rated concurrently by two physical therapists in a single testing session. Sessions were video recorded and rated by the same raters viewing the video 7–10 days later. Raters completed a survey assessing feasibility of conducting the dual-task measures in patients with TBI in inpatient rehabilitation. Data were analyzed by calculating ICC(2, 1) for inter-rater reliability and ICC(3, 1) for intra-rater reliability. Results : All dual-task measures (WWTT, mWART, TUG-COG) had excellent inter-rater and intra-rater reliability. Raters considered dual-task measures feasible for patients with TBI during inpatient rehabilitation. Conclusions : The WWTT, mWART, and TUG-COG have excellent reliability and appear clinically feasible for incorporation into clinical practice in inpatient rehabilitation following TBI.